Facility versus unit level reporting of quality indicators in nursing homes when performance monitoring is the goal. Issue 2 (12th February 2014) - Norton, Peter G; Murray, Michael; Doupe, Malcolm B; Cummings, Greta G; Poss, Jeff W; Squires, Janet E; Teare, Gary F; Estabrooks, Carole A
Abstract : Objectives: To demonstrate the benefit of defining operational management units in nursing homes and computing quality indicators on these units as well as on the whole facility. Design: Calculation of adjusted Resident Assessment Instrument – Minimum Data Set 2.0 (RAI–MDS 2.0) quality indicators for: PRU05 (prevalence of residents with a stage 2–4 pressure ulcer), PAI0X (prevalence of residents with pain) and DRG01 (prevalence of residents receiving an antipsychotic with no diagnosis of psychosis), for quarterly assessments between 2007 and 2011 at unit and facility levels. Comparisons of these risk-adjusted quality indicators using statistical process control (control charts). Setting: A representative sample of 30 urban nursing homes in the three Canadian Prairie Provinces. Measurements: Explicit decision rules were developed and tested to determine whether the control charts demonstrated improving, worsening, unchanging or unclassifiable trends over the time period. Unit and facility performance were compared. Results: In 48.9% of the units studied, unit control chart performance indicated different changes in quality over the reporting period than did the facility chart. Examples are provided to illustrate that these differences lead to quite different quality interventions. Conclusions: Our results demonstrate the necessity of considering facility-level and unit-level measurement when calculating quality indicators derived from the RAI–MDS 2.0 data, and quite probably from any RAI measures.